Telocytes in inflammatory bowel diseases: contributions to pathology and therapeutic potentials - Panganiban, Ronaldo Paolo; McAninch, Christina; Chulkina, Marina; Pinchuk, Irina V. (Frontiers in Cell and Developmental Biology, 2025)
Telocytes, a novel mesenchymal cell population, are characterized by their distinctive long and slender projections known as telopodes and have garnered significant interest since their formal introduction to the literature in 2010. These cells have been identified in various tissues, including the gastrointestinal (GI) tract, where they are suggested to play important roles in maintaining structural integrity, immune modulation, and barrier function. Inflammatory bowel diseases (IBD), which include Crohn’s disease (CD) and ulcerative colitis (UC), are characterized by chronic inflammation and fibrosis. While limited information is available on the fate of telocytes in this group of diseases, it has been suggested that loss/plasticity of telocytes can be among the key factors contributing to their pathogenesis. This review focuses on the current understanding of telocytes, their structural features, and their distribution within the GI tract under gut homeostasis and IBD. We also discuss the roles of these cells in immune regulation and intestinal repair. We highlight evidence implicating telocytes in the pathogenesis of IBD and other chronic inflammatory diseases that share similar pathophysiological processes with IBD. Lastly, we discuss the current challenges in gut telocyte biology and the potential therapeutic implications of telocytes in IBD.